2015
DOI: 10.1096/fj.15-276618
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodium actin is incompletely folded by heterologous protein‐folding machinery and likely requires the native Plasmodium chaperonin complex to enter a mature functional state

Abstract: Actin filament turnover underpins several processes in the life cycle of the malaria parasite, Plasmodium falciparum. Polymerization and depolymerization are especially important for gliding motility, a substrate-dependent form of cell movement that underpins the protozoan parasite’s ability to disseminate and invade host cells. To date, given difficulties in extraction of native actins directly from parasites, much of our biochemical understanding of malarial actin has instead relied on recombinant protein ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 58 publications
(115 reference statements)
1
25
0
Order By: Relevance
“…Since apicomplexan actin cannot be functionally heterologously expressed (Olshina et al, 2016), we used skeletal chicken actin to estimate the binding characteristics of Cb to F-actin. Recombinant Cb with a C-terminal 6-His tag (rCb) was expressed and purified from bacteria (Figure 5A,B).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Since apicomplexan actin cannot be functionally heterologously expressed (Olshina et al, 2016), we used skeletal chicken actin to estimate the binding characteristics of Cb to F-actin. Recombinant Cb with a C-terminal 6-His tag (rCb) was expressed and purified from bacteria (Figure 5A,B).…”
Section: Resultsmentioning
confidence: 99%
“…Since then, polymerization kinetics of heterologously expressed apicomplexan actin showed that it polymerized in an unusual isodesmic process, in contrast to conventional eukaryotic actin (Skillman et al, 2013). These findings have been recently questioned, as heterologously expressed apicomplexan actin was shown to be misfolded (Olshina et al, 2016). In parallel, a number of recent genetic studies have demonstrated important functions of parasite actin during intracellular development, including maintenance of the apicoplast (Andenmatten et al, 2013; Egarter et al, 2014), daughter cell replication (Haase et al, 2015) and motility of secretory organelles (Heaslip et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous polymerisation studies used G-actin produced in heterologous protein expression systems. However, a recent study demonstrated that apicomplexan actin is not properly folded when heterologously expressed due to differences in the chaperonin T-complex [50]. Furthermore, a recent study suggests that Toxoplasma actin is capable of forming F-actin structures in vivo that depend on a critical monomer concentration and demonstrates that F-actin is involved in multiple essential processes during intracellular parasite growth such as daughter cell assembly, vacuole organisation and parasite egress [28].…”
Section: Discussionmentioning
confidence: 99%